Maca (Lepidium meyenii Walp.) on semen quality parameters: A systematic review and meta-analysis - Lee, Hye Won; Lee, Myeong Soo; Qu, Fan; Lee, Je-Won; Kim, Eunseop (Frontiers in Pharmacology, 2022)
Background: This study aimed to examine the evidence for Lepidium meyenii Walp. [Brassicaceae], known as Maca, in improving semen quality. Methods: A total of ten databases were searched for randomized controlled trials (RCTs) to examine the parameters for improvements in semen quality, irrespective of the type of Lepidium meyenii W. The risk of bias among the studies was evaluated per the Cochrane criteria. Results: Five RCTs met all of the inclusion criteria. Three RCTs showed mixed efficacy of maca on semen quality parameters, including sperm concentration and sperm motility, in men experiencing infertility. The meta-analysis also failed to show the efficacy of maca on sperm concentration compared to the placebo (weighted mean difference, WMD, 2.22, 95% CI -2.94 to 7.37, p =0.4). Two other RCTs also showed mixed effects of maca on several semen quality parameters in healthy men. Conclusion: The evidence from the included studies suggests unclear effects of maca on semen quality parameters in both men experiencing infertility and healthy men. However, the total number of RCTs and the total sample size were too small to draw firm conclusions.